1986
DOI: 10.1002/bjs.1800730817
|View full text |Cite
|
Sign up to set email alerts
|

Failure to improve survival by improved diagnostic techniques in patients with malignant jaundice

Abstract: In a consecutive series of 118 patients with malignant obstructive jaundice at North Tees General Hospital only 70 patients were adjudged fit to undergo surgery. Tumour resection was possible in only four patients. Palliative bypass was performed in 45 patients while 21 patients had no procedure other than an exploratory laparotomy. In contrast to the accuracy of investigation the results of surgery have been poor with considerable mortality (42.8 per cent) and lack of long-term survivors. The results emphasiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
6
0
2

Year Published

1988
1988
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 13 publications
2
6
0
2
Order By: Relevance
“…Thus, unfortunately, the prognosis of patients presenting with jaundice caused by hepatobiliary cancer obstructing the biliary ducts (or due to liver metastases) does not seem to have improved during the last 3 decades. The most common cause of malignant obstructive jaundice in the current study was pancreatic cancer, which is in agreement what was reported in earlier studies 3, 11–15. The poor prognosis of patients with pancreatic cancer is well known, but operative mortality is very low nowadays, and some series have reported 5‐year survival rates in the range of 10%–30% 16–20.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Thus, unfortunately, the prognosis of patients presenting with jaundice caused by hepatobiliary cancer obstructing the biliary ducts (or due to liver metastases) does not seem to have improved during the last 3 decades. The most common cause of malignant obstructive jaundice in the current study was pancreatic cancer, which is in agreement what was reported in earlier studies 3, 11–15. The poor prognosis of patients with pancreatic cancer is well known, but operative mortality is very low nowadays, and some series have reported 5‐year survival rates in the range of 10%–30% 16–20.…”
Section: Discussionsupporting
confidence: 92%
“…Studies published more than 20 years ago are available on the etiology and prognosis of these patients, reflecting the diagnostic techniques and hospital practice at that time 6–9. Furthermore, more recently published studies report the etiological spectrum of patients with obstructive jaundice in Africa and India 10–12. In our study population, 154 of 241 patients (64%) had a malignancy, which is remarkably similar to the 61% and 65% of cases of obstructive jaundice due to malignancy reported in studies published more than 25 years ago from Denmark and Spain, respectively 6–7, 14…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Our survival data showed a 5‐year survival of 27.6% in Stage I in the nonpathologically confirmed group compared to 4% in the pathologically confirmed group. Other studies have shown that in pathologically confirmed cases, whether treated by resection, bypass procedures, or irradiation, the mean survival has usually been less than 1 year with a range from 2.5–13 months 9,10,17‐21 . Our survival data suggest that in a substantial number of cases the clinical diagnosis of carcinoma of the pancreas is incorrect.…”
Section: Discussionmentioning
confidence: 57%